The Migraine and plant antioxidant: Review article - Al-Fayyadh, Mohanad Salam Majeed; Kefah H. Ismael; Ali J.R.Al-Saady (University of Thi-Qar Journal of Science, 2023)
Even though the pathophysiology of migraine has been the subject of many works, the precise molecular mechanism regarding the disturbances that underlie migraine remains unknown. Additionally, it is thought that oxidative stress contributes significantly to migraine development. For many years, the idea that migraine sufferers experience oxidative stress was addressed. The so-called nutraceutics, which include antioxidants, have received a lot of attention in the last few years among the substances which may be utilized to cure migraines. Antioxidants that are supplied with the food prevent the oxidative stress through suppressing the propagation, initiation, and actual oxidative chain reaction. The agents now being utilized to prevent migraines do in fact have certain antioxidative activity. Antioxidants that have been addressed in this research are growing more regularly utilized through the migraine sufferers not just because of low or even lack of side effects, yet as well due to their efficiency (shortening of an episode duration or reduced frequency of migraine episodes).